Bottom‐Up Designed Porous Coaxial Twin‐Electrodes for Efficient Redox Cycling. (30th November 2022) - Šafarik, Tatjana; Karajić, Aleksandar; Reculusa, Stéphane; Bartlett, Philip N.; Mano, Nicolas; Kuhn, Alexander
Abstract: Redox cycling (RC) is a powerful tool capable of amplifying faradaic currents in electroanalytical measurements, thus allowing an enhancement of sensitivity through fast multiple sequential oxidation and reduction reactions of a redox‐active analyte. Present state‐of‐the‐art RC devices are mostly based on planar electrode geometries either in 2D or 3D configurations, requiring cleanroom facilities and expensive microfabrication techniques. Here, the electrochemical elaboration and characterization of a 3D coaxial macroporous twin‐electrode is reported, obtained by following a low‐cost bottom‐up approach. A nanoengineered highly organized porous material is the basis for the design of two threaded cylindrical porous gold microelectrodes with a gap in the micrometer range that can be fine‐tuned. The potentials of the outer and inner electrodes are biased at values above and below the redox potential of the analyte so that a given molecule can participate several times in the electron exchange reaction by shuttling between both electrodes. The resulting signal amplification, combined with a straightforward synthesis strategy of the electrode architecture, allows envisioning numerous (bio)electroanalytical applications. Abstract : Following a low‐cost bottom‐up approach, two threaded porous cylindrical microelectrodes are generated in a coaxial configuration, which results in a very compact functional device for redox cycling. Efficient signal amplification of the analyte is obtained due to the small gap between the two electrodes, a high surface area, and confined geometry.